Aerodynamic variation with differences in the number of riders in a cycling group - Shirasaki, K.; Yamanobe, K.; Akashi, K.; Takashima, W. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
In when riding in a group during cycling competitions, cyclists may become located side-by-side during positioning, rotation, and overtaking. The primary objective of this study was to analyze aerodynamic variation with differences in the number of riders (1 and 3) while cycling in parallel. It was assumed that the last cyclist would be riding in parallel with the immediate leading cyclist in the group. Wind tunnel experiments were implemented using a static mannequin and athletes as participants. A floor-mounted 6-component force balance was employed for conducting the measurements, and the athlete sat on a bicycle mounted on a bicycle stand. Experiments were subsequently conducted on groups comprising 2 riders (2R) and 4 riders (4R). The aerodynamic drag of the last rider (i.e., the mannequin) was measured for a wind speed of 16.67 m/s and for various relative spatial positions with respect to the front end of the immediate leading rider`s front wheel as the origin (longitudinal distance X = -1.38 m-0.07 m, lateral distance Y = 0.25 m-0.90 m; X = -1.38 m was applied solely when Y = 0.90 m for the case of 2R). The results indicated that at Y = 0.75 m-0.90 m, the drag of the last rider for both the 2R and 4R cases was equal to or higher than that for the single state. At Y = 0.50 m, the drag in the 2R case was equal to or higher than that for the single state (maximum value, 108.5% of the single state), whereas the drag in the 4R case was less (87.8-95.1%). It was also found that when a parallel cyclist approached a riding group comprising 3 or more cyclists, it was possible to decrease the drag to a value less than for the single state by riding in a position strictly adjacent to the riding group.